The role of affects in predicting the success of expert table tennis players - Abdoshahi, M.; Limoochi, S.; Shemshaki, A. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The relationship between psychological variables and skill performance has been a key matter for sports psychologists for many years. For example, in the multidimensional anxiety theory (Martens et al., 1990), it is assumed that cognitive anxiety has a negative linear relationship, somatic anxiety has an Inverted-U shape relationship, and self-confidence has a positive linear relationship with the performance. Therefore, the purpose of the present study was to predict the success (Winner or loser) of table tennis athletes based on arousal, self-confidence, cognitive and somatic anxiety. The participants were 56 expert table tennis players (28 men and 28 women, mean age of 25.36 ± 2.70 years) who participated in Iran Super League competitions. Self-confidence and somatic anxiety were measured by two items of the Mental Readiness Form (MRF-3; Krane, 1994), and cognitive anxiety and arousal levels were assessed by "sport grid-revised" (Ward & Cox, 2004), 15 minutes before the start of the first match in the morning. Logistic regression was used for prediction. Results revealed that one model with two factors was significant. Cognitive anxiety, and Self-confidence have been able to significantly predict winning in the match. This model supports the part of the multidimensional anxiety theory. Also, these findings established the important effects of psychological variables on the final success of the champions.